Antiangiogenic Therapies and Extracranial Metastasis in Glioblastoma: A Case Report and Review of the Literature. (23rd June 2015) - Khattab, Mohamed H.; Marciscano, Ariel E.; Lo, Simon S.; Lim, Michael; Laterra, John J.; Kleinberg, Lawrence R.; Redmond, Kristin J.
Abstract : We present a case report of a patient with glioblastoma multiforme (GBM) complicated by extracranial metastasis (ECM) whose survival of nearly four years surpassed the anticipated life expectancy given numerous negative prognostic factors including EGFRvIII-mutation, unmethylated MGMT promoter status, and ECM. Interestingly, while this patient suffered from locally aggressive disease with multiple intracranial recurrences, the proximal cause of death was progressive extracranial disease and complications related to pulmonary metastases. Herein, we review potential mechanisms of ECM with an emphasis upon glioblastoma molecular and genetic profiles and the potential implications of targeted agents such as bevacizumab.